Kryminologia konsensualna czy konfliktowa? Spór o koncepcję - Krajewski, Krzysztof (Wydział Prawa i Administracji UAM, 1987)
Since late sixties one can observe in criminological literature significant change of the assumptions about society and social order. This change may be described as the turn from the assumption of normative consensus towards the assumption of social conflict, which is of very significant consequences for sociological conceptions of crime and deviance. Because of this it is possible to speak about two paradigms within criminological thought: consensual and conflict ones. Consensual Paradigm assumes normative consensus as the main source of social order. Because of this, deviance is treated as an indicator of the lack of adjustment, product of individual or social pathology. Within conflict paradigm, which assumes that social order results from coercion, society is perceived as the aggregation of many social groups with different and conflicting cultures. In such situation deviance constitutes normal behavior of individuals acting in accordance with values and norms of the groups they belong to, which under certain conditions may be stigmatised as deviant or criminal. Sources of stigmatisation and criminalisation are main problems for contemporary conflict criminology. They are explained in terms of social conflict, where criminal law is perceived as the tool of power elites in subduing other groups. Because of this conflict, criminology abandones traditional etiological questions. Instead, it tries to develop critical sociology of criminal law and criminal justice. The main problem about this approach is whether it is really impossible to reconcile it with traditional consensus criminology. It seems that it is possible. Consensus and conflict constitute two aspects of every society. Which one prevails depends on circumstances. The main task is to ascertain in what situations which approach constitutes better and more adequate tool of describing deviant and criminal phenomena.
Consensual criminology or conflict criminology? A conception in dispute